Analysis of the influence of branding, Product Quality and Live Streaming on Purcasing Decision for Skin1004 on Shopee - Anneke Ria Choirunnisa; Satrio Sudarso; Lilik Indayani (Indonesian Journal of Islamic Economics and Finance, 2026)
This study aims to determine the influence of branding, product quality, and live streaming on purchasing decisions for Skin1004 toner products on Shopee. This study is a quantitative study with a survey method using a purposive sampling technique. The sample collected was 100 respondents who had purchased Skin1004 toner products through the Shopee platform. This study used multiple linear regression data analysis techniques with the help of the SPSS version 26 program. The results showed that branding, product quality, and live streaming had a positive and significant influence both partially and simultaneously on purchasing decisions for Skin1004 toner products on Shopee. This indicates that the better the branding, product quality, and live streaming carried out, the consumer's purchasing decisions for Skin1004 toner products on Shopee will also increase. The variables of branding, product quality, and live streaming together were able to explain 72.3% of the variation in purchasing decisions, with the branding variable having the largest regression coefficient (Beta) making it the most dominant factor influencing purchasing decisions.